2014
DOI: 10.1063/1.4894509
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis and compensation behaviors of spin-3/2 cylindrical Ising nanotube system

Abstract: An effective-field theory with correlations has been used to study the hysteresis, susceptibility and compensation behaviors of the spin-1 hexagonal Ising nanowire (HIN) with core-shell structure. The effects of the temperature, crystal field, core-shell interfacial coupling and shell surface coupling are investigated on hysteresis and compensation behaviors, in detail. When the core-shell interfacial coupling is weak, the double and triple hysteresis loops can be seen in the system. The hysteresis loops have … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 111 publications
(40 reference statements)
3
11
0
Order By: Relevance
“…In this range of D/J s , it is worthwhile to notice that the phase diagrams are very sensitive to the change of D/J s ; that is, when we increase D/J s , this threshold value of J σ /J s shifts to lower values of J σ /J s , in contrast the critical temperature increases with D/J s . It is important to mention that in this range also, we can have two kinds of phase diagrams, in the first one [31], where the effective field theory has been used to study spin-3/2 cylindrical Ising nanotube system. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this range of D/J s , it is worthwhile to notice that the phase diagrams are very sensitive to the change of D/J s ; that is, when we increase D/J s , this threshold value of J σ /J s shifts to lower values of J σ /J s , in contrast the critical temperature increases with D/J s . It is important to mention that in this range also, we can have two kinds of phase diagrams, in the first one [31], where the effective field theory has been used to study spin-3/2 cylindrical Ising nanotube system. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The compensation point has also been obtained theoretically in Refs. [15,28,35,36] and experimentally by Estrader et al [3] for the magnetization of the core/shell particles based on F e-oxides and Mn-oxides. We can clearly see, at zero temperature, that the M T curves have three saturation magnetizations M sat = −0.218, −0.342, and −0.369 when the core/shell antiferromagnetic interfacial coupling are selected as r cs = −0.1, −0.3, and −0.5, respectively, which indicate that the saturation value of the total longitudinal magnetization decreases with the decrease of r cs .…”
Section: Numerical Results and Discussionmentioning
confidence: 98%
“…On the other hand, the magnetic and thermodynamic properties of these NP systems have been studied by a variety of techniques, such as the mean-field theory (MFT) [13], effectivefield theory (EFT) with correlations [14][15][16][17], Green functions (GF) formalism [18], variational-cumulant expansion (VCE) [19], and Monte Carlo (MC) simulations [20][21][22]. Based on the EFT with correlations, Canko et al [23] have investigated the magnetic and the thermodynamic properties of a cylindrical spin-1 Ising nanotube, and they have also investigated the magnetic susceptibility, specific heat, internal energy, and free energy of a cylindrical mixed spin-1 2 and spin-1 Ising nanotube [24].…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been studied the behavior of hysteresis and compensation in cylindrical Ising nanotube systems. Kocakaplan et al, [17] observed that areas of hysteresis loops decrease as the temperature increases and disappears at certain temperatures. Also, showing the different forms that hysteresis loops can exhibit.…”
Section: Introductionmentioning
confidence: 99%
“…The possible applications in the design of new materials motivate the study of nanoparticles with high spin values. The behavior of hysteresis has been investigated for cylindrical nanowires within the effective-field theory (EFT) varying the interaction (ferromagnetic and antiferromagnetic) [17]. Also, it has been studied the behavior of hysteresis and compensation in cylindrical Ising nanotube systems.…”
Section: Introductionmentioning
confidence: 99%